The Effect of Using Pop-Up Book Learning Media on Students' Motivation and Learning Outcomes in Natural and Social Science Subjects - Nahari, Laila; Novalita, Rahmi; Fitrah, Hariki (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This research aims to describe; 1) the influence of using pop-up book learning media on student learning motivation, 2) the influence of using pop-up book learning media on student learning outcomes, and 3) the influence of using pop-up book learning media on student motivation and learning outcomes. This type of research is quasi-experimental research using a quantitative approach. The subjects of this research were 30 students in class V of Silih Nara 4 Elementary School. This research design uses One Group Pretest-Posttest Design. Data collection techniques use observation, questionnaires and documentation. The analysis technique uses a simple linear regression analysis test. The research results show that; a) there is a significant influence of the use of pop-up book learning media on student learning motivation, b) there is a significant influence of the use of pop-up book learning media on student learning outcomes, c) there is a significant influence of the use of pop-up book learning media on student motivation and learning outcomes.